Visual exploratory activity and resultant behavioural analysis of youth midfield soccer players - Eldridge, D.; Pulling, C.; Robins, M. (Journal of Human Sport & Exercise, 2013)
The purpose of this study was to examine the effects of visual exploratory activity, prior to receiving the ball in the middle third of the pitch, on the actions of youth midfield soccer players. The visual exploratory activity of three youth central midfield players was examined using a player cam approach, which in turn, was related to each player`s actions, after receiving the ball, through the use of a wide angle perspective. SportsCode Elite software was used to analyse all player actions post-event. Players participated in five training games, each 20 minutes in duration. The player`s actions were divided into five themes: (1) maintaining possession, (2) loss of possession, (3) field location of maintained possessions (4) defensive pressure, and, (5) turning. Associations between visual exploratory activity and each of the resultant behavioural themes were examined using a chi-squared test (p<0.05). The findings of the study revealed that the players performed more forward passes, executed more passes into the attacking half, performed more turns when opportunities arose, and experienced less defensive pressure when performing visual exploratory activity prior to receiving the ball (p<0.01). There is evidence to suggest that coaches should encourage players to perform visual exploratory activity prior to receiving possession of the football. Moreover, coaches should be acutely aware that visual exploratory activity can influence the technical and tactical aspects of performance, and, consequently, this aspect should be considered an important facet to aid player development.